Begonia benitotanii (section Petermannia, Begoniaceae) a new species endemic to the Philippine island of Bucas Grande - Rubite, Rosario Rivera; Brillantes, Rochelle Yongque; Tandang, Danilo N.; Moran, Cecilia B.; Rule, Mark Gregory Q.; Lin, Chei-Wei (Phytotaxa, 2021)
In 2011 and later in a 2018 field survey, an unknown Begonia species allied to taxa in section Petermannia was found in Bucas Grande Island. After thorough studies of the living plant, literature, and herbarium specimens we name the new species Begonia benitotanii, to honor Dr. Benito C. Tan, the internationally known Filipino muscologist. In 2011, there were two populations observed, each of about 300 individuals in a 100 m area. During recent fieldwork, one population was found decimated while the other was reduced to just about 50 individuals. The site is being converted into coconut, banana, and rice plantations. The area is not currently protected under the country’s National Integrated Protected Areas System by the Department of Environment and Natural Resources. According to the IUCN red list categories and criteria, B. benitotanii is hereby proposed to be placed under the Critically Endangered (CR) category.